Evaluasi Sistem Penyaliran Tambang Batubara di Pit 1 PT. Benal Aiti Bara Perkasa Jobsite Jpc Desa Pemusiran Kecamatan Mandiangin Kabupaten Sarolangun Provinsi Jambi - Rusli Har; silvi anadia (Journals Mining Engineering : Bina Tambang, 2022)
ABSTRACT Silvi Anadia: Evaluasi Sistem Penyaliran Tambang Batubara di Pit 1 PT. BenalAiti Bara Perkasa Jobsite Jpc Desa Pemusiran Kecamatan Mandiangin Kabupaten Sarolangun Provinsi Jambi              High rainfall in the mining industry can affect mining operations, an optimal form of effort for handling air entering the mining area through a form of mine drainage system study. The purpose of the research is to control runoff water entering the mine openings so that the mining process is not disturbed. The calculation of the planned day rainfall to determine the use of gumbel distribution, the planned rainfall is 186.290501 mm/day for a 25 year return period, the annual runoff discharge with a 25 year return period is 0.30804 m3/s. Based on the results of the analysis between the planned annual runoff discharge and the pump's capacity, there must be at least 2 selwood pumps available to cope with high-intensity rain, if not in the rainy season, one pump is sufficient to keep the air from disturbing mining activities. The designed sump has a base side of 90 m while the surface side of the sump is 84 m with a depth of 5 meters and a wall angle of 60° sump has a volume of 37,890 m3. The dimensions of the open channel that will be used are trapezoidal in shape because it is easier to manufacture Keyword : Precipitation, sump, pump, open channel,